Piezoelectrically and Capacitively Transduced Hybrid MEMS Resonator with Superior RF Performance and Enhanced Parasitic Mitigation by Low-Temperature Batch Fabrication - Adnan Zaman; Ugur Guneroglu; Abdulrahman Alsolami; Jing Wang (Applied Sciences)
This study investigates a hybrid microelectromechanical system (MEMS) acoustic resonator through a hybrid approach to combine capacitive and piezoelectric transduction mechanisms, thus harnessing the advantages of both transducer technologies within a single device. By seamlessly integrating both piezoelectric and capacitive transducers, the newly designed hybrid resonators mitigate the limitations of capacitive and piezoelectric resonators. The unique hybrid configuration holds promise to significantly enhance overall device performance, particularly in terms of quality factor (Q-factor), insertion loss, and motional impedance. Moreover, the dual-transduction approach improves the signal-to-noise ratio and reduces feedthrough noise levels at higher frequencies. In this paper, the detailed design, complex fabrication processes, and thorough experimental validation are presented, demonstrating substantial performance enhancement potentials. A hybrid disk resonator with a single side-supporting anchor achieved an outstanding loaded Q-factor higher than 28,000 when operating under a capacitive drive and piezoelectric sense configuration. This is comparably higher than the measured Q-factor of 7600 for another disk resonator with two side-supporting anchors. The hybrid resonator exhibits a high Q-factor at its resonance frequency at 20 MHz, representing 2-fold improvement over the highest reported Q-factor for similar MEMS resonators in the literature. Also, the dual-transduction approach resulted in a more than 30 dB improvement in feedthrough suppression for devices with a 500 nm-thick ZnO layer, while hybrid resonators with a thicker piezoelectric layer of 1300 nm realized an even greater feedthrough suppression of more than 50 dB. The hybrid resonator integration strategy discussed offers an innovative solution for current and future advanced RF front-end applications, providing a versatile platform for future innovations in on-chip resonator technology. This work has the potential to lead to advancements in MEMS resonator technology, facilitating some significant improvements in multi-frequency and frequency agile RF applications through the original designs equipped with integrated capacitive and piezoelectric transduction mechanisms. The hybrid design also results in remarkable performance metrics, making it an ideal candidate for integrating next-generation wireless communication devices where size, cost, and energy efficiency are critical.